2021
DOI: 10.1038/s41398-021-01342-6
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic dimensions of psychopathology explain individuals’ unique deviations from normative neurodevelopment in brain structure

Abstract: Psychopathology is rooted in neurodevelopment. However, clinical and biological heterogeneity, together with a focus on case-control approaches, have made it difficult to link dimensions of psychopathology to abnormalities of neurodevelopment. Here, using the Philadelphia Neurodevelopmental Cohort, we built normative models of cortical volume and tested whether deviations from these models better predicted psychiatric symptoms compared to raw cortical volume. Specifically, drawing on the p-factor hypothesis, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 68 publications
6
53
0
1
Order By: Relevance
“…The approach has been used to map the heterogeneous phenotypes of schizophrenia, bipolar disorder, ADHD, and autism (Wolfers et al, 2018(Wolfers et al, , 2020Zabihi et al, 2019). Applying this approach to transdiagnostic dimensions of psychopathology, recent work has further shown that modelling cortical brain features as deviations from normative neurodevelopment improves prediction of psychiatric symptoms in out-of-sample testing (Parkes, Moore, Calkins, Cook, et al, 2021). Importantly, more generally deviations can also take the form of acceleration or delay of 'typical' development, which can be explained by a variety of factors including socioeconomic status (Tooley et al, 2021).…”
Section: Emergence Across Timementioning
confidence: 99%
“…The approach has been used to map the heterogeneous phenotypes of schizophrenia, bipolar disorder, ADHD, and autism (Wolfers et al, 2018(Wolfers et al, , 2020Zabihi et al, 2019). Applying this approach to transdiagnostic dimensions of psychopathology, recent work has further shown that modelling cortical brain features as deviations from normative neurodevelopment improves prediction of psychiatric symptoms in out-of-sample testing (Parkes, Moore, Calkins, Cook, et al, 2021). Importantly, more generally deviations can also take the form of acceleration or delay of 'typical' development, which can be explained by a variety of factors including socioeconomic status (Tooley et al, 2021).…”
Section: Emergence Across Timementioning
confidence: 99%
“…The rapidly growing use of predictive modelling in neuroimaging to map brain-behavior relationships has yielded numerous important advances in recent years. Studies have investigated how preprocessing (Li et al 2019), data transformation (Parkes et al 2021), predictive algorithms (He, Kong, et al 2020), neuroimaging features (Dhamala, Jamison, Jaywant, Dennis, et al 2021;Greene et al 2018), model translation , parcellation choices (Dhamala, Jamison, Jaywant, Dennis, et al 2021) 2021), but also generalizable across datasets (Scheinost et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly growing use of predictive modelling in neuroimaging to map brain-behavior relationships has yielded numerous important advances in recent years. Studies have investigated how preprocessing (Li et al 2019), data transformation (Parkes et al 2021), predictive algorithms (He, Kong, et al 2020), neuroimaging features (Dhamala, Jamison, Jaywant, Dennis, et al 2021; Greene et al 2018), model translation (He, An, et al 2020), parcellation choices (Dhamala, Jamison, Jaywant, Dennis, et al 2021), sample sizes (Marek et al 2020), and phenotype selection (Chen et al 2020) can influence neuroimaging-based predictions of individual behaviors. Unfortunately, these studies have in large part relied on single datasets of healthy young adults to train and evaluate model performance, even though it is becoming increasingly evident that models must be not only replicable and reliable within a dataset (Tian and Zalesky 2021), but also generalizable across datasets (Scheinost et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a distribution of the classification performance was further computed for each seed by subtracting the classification accuracies of the permutation tests from those derived from the true labels within the same iteration. Upon this distribution, a 99% confidence interval (CI) was calculated to see if the lower CI bound was above 0, indicating better-than-chance-level classification performance (see a similar approach in [53]). Finally, for the seed-specific FC patterns with classification results significantly outperforming the permutation tests (i.e., p corrected < 0.5) and demonstrating a positive CI, the effect size was further measured using Cohen’s d , where larger magnitudes indicate stronger classification performance.…”
Section: Methodsmentioning
confidence: 99%